Consequências psicológicas vivenciadas por mulheres sobreviventes das torturas praticadas pelos aparatos e agentes do Estado durante o período da Ditadura Militar brasileira - Monteiro, Julie Ane Notari (Universidade Federal de São Carlos, 2023)
This research project aims to carry out an analysis of the psychological consequences that torture brought to women who were political prisoners during the period of the Brazilian Military Dictatorship, which occurred between the years 1964 and 1985. To this end, semi-structured interviews were carried out with women who have suffered such violation. The starting hypotheses were that these women may have experienced impacts on the establishment and maintenance of emotional bonds and loving relationships, difficulties in building a healthy sexual life and development of psychopathologies, such as Post-Traumatic Stress Disorder (PTSD), Generalized Anxiety Disorder (GAD) and Major Depressive Disorder. As a form of analysis, Content Analysis was used based on the participants' reports. Such data analysis confirmed the hypotheses raised by the initial project: women had impacts on the establishment and maintenance of emotional bonds and loving relationships, difficulties in building a healthy sexual life and development of psychopathologies, such as Post-Traumatic Stress Disorder (PTSD), Generalized Anxiety Disorder (GAD) and Major Depressive Disorder. Future studies should cover a larger portion of the population that also suffered during this period: LGBTQIA+ people, black people and the indigenous population. Furthermore, it is extremely necessary to investigate how torture and violation of Human Rights have been validated by the State today.
Psychological consequences experienced by women survivors of torture practiced by State apparatuses and agents during the period of the Military Dictatorship brazilian
Keywords: Consequências psicológicas; Violência sexual; Ditadura militar; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA